Perennial crops can complement semi-natural habitats in enhancing ground beetle (Coleoptera: Carabidae) diversity in agricultural landscapes - Meina Wang (Elsevier, 2021)
Agricultural intensification has caused losses of global biodiversity and associated ecological services. Agroecological landscape assessments are therefore often based on the area of remaining semi-natural habitats due to their ability to promote biodiversity. Due to their structural diversity and often less intensive management in comparison to annual crops, perennial cropland could fulfil similar roles. However, comparisons of the ability of perennial cropland versus semi-natural habitat to maintain agricultural diversity are scarce. Here, we conduct such an assessment, in comparing functional group-specific patterns in ground beetles (Coleoptera: Carabidae) as indicators of anthropogenic land-use impacts on biodiversity and biological pest control. Carabid assemblages were compared between annual cropland (56 plots), perennial cropland (24 plots) and semi-natural habitats (74 plots) of varying plant diversity across nine study regions situated in Eastern China. Our results indicated that perennial crops sustained a greater carabid species richness than semi-natural habitats, whereas assemblages of semi-natural habitats contained greater proportions of large and predatory carabids. Plant species richness positively affected the overall diversity of carabids, with the strongest effects again observed in perennial cropland. Abundance-based and species-based proportions of large carabids were positively linked to plant diversity in perennial cropland and semi-natural habitats, but negatively in annual cropland. A similar response was observed for predatory carabid abundance. Perennial crops might therefore fulfil complementary roles to semi-natural habitats in agricultural biodiversity conservation. Given common trade-offs between biodiversity conservation and agricultural production, promoting perennial cropland in particular in combination with management that increases plant diversity, could enable increases in the sustainability of agricultural production systems particularly in areas with high food demand, but limited availability of arable land. Notwithstanding, semi-natural habitats remain crucial particularly with view of enhancing biological pest control services.